2018
DOI: 10.3389/fmicb.2018.02208
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Human Mycobiota: A Comparison of Small Subunit rRNA, ITS1, ITS2, and Large Subunit rRNA Genomic Targets

Abstract: Interest in the human microbiome has increased dramatically in the last decade. However, much of this research has focused on bacteria, while the composition and roles of their fungal counterparts remain less understood. Furthermore, a variety of methodological approaches have been applied, and the comparability between studies is unclear. This study compared four primer pairs targeting the small subunit (SSU) rRNA (18S), ITS1, ITS2, and large subunit (LSU) rRNA (26S) genomic regions for their ability to accur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(71 citation statements)
references
References 100 publications
2
68
0
1
Order By: Relevance
“…Based on the data presented, ITS-sequencing has been established at our center as a routine investigation in addition to all the other diagnostic tools, like culture, biomarker testing including recently released Aspergillus lateral flow device tests and PCRs. In some studies, the sequencing of amplicons of 18S or ITS2 genes outperformed the results created by using ITS1 targets, as used in our study [34,35].…”
Section: Discussionmentioning
confidence: 69%
“…Based on the data presented, ITS-sequencing has been established at our center as a routine investigation in addition to all the other diagnostic tools, like culture, biomarker testing including recently released Aspergillus lateral flow device tests and PCRs. In some studies, the sequencing of amplicons of 18S or ITS2 genes outperformed the results created by using ITS1 targets, as used in our study [34,35].…”
Section: Discussionmentioning
confidence: 69%
“…Nevertheless, these targets are commonly used in the literature (see Table 1), particularly ITS1, which was suggested as the universal barcoding target for fungi [82]. A few studies have analysed the accuracy of ITS1 sequencing using mock communities and found significant bias for some groups [81,83,84]. Variation in amplicon size may contribute to such bias, as the commonly used ITS1 amplicon is known to contain an intron in some fungi.…”
Section: Sequencing Methodsologiesmentioning
confidence: 99%
“…Hoggard et al assessed the use of four amplicon targets (ITS1, ITS2, SSU and LSU) with mock communities consisting of known members of the human mycobiota [83]. This analysis found an overrepresentation of Candida albicans and Trichosporon dermatis with all targets.…”
Section: Sequencing Methodsologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…(GCTGCGTTCTTCATCGATGC) primers for ITS1 [36] and forward fITS9 (GAACGCAGCRAAIIGYGA) and reverse ITS4 (TCCTCCGCTTATTGATATGC) primers (Sigma-Aldrich, U.K.) for ITS2 ( [37], [38] respectively) were used in combination with 8 bp unique tags (Supporting Table S2). The expected amplicon size was ~ 250-600 bp for ITS1 [39,40] and ~ 240-460 for ITS2. Primers and tags used for the subsequent analyses both for ITS1 and for ITS2 amplifications have been listed in Supporting Table S2.…”
Section: Dna Extraction Amplification and Sequencingmentioning
confidence: 99%